Pengaruh Responssive dan Empathy terhadap Kualitas Pelayanan Publik di Kantor Kementerian Agama Kota Surabaya - Fikri Aldryan Putra Maksum; Kristyan Dwijosusilo; Widyawati, Widyawati (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study evaluates the quality of public services at the Office of the Ministry of Religious Affairs in Surabaya by focusing on two SERVQUAL dimensions: responsiveness and empathy. The research is motivated by public complaints related to slow service processes, unclear information delivery, and insufficient empathy from service officers. Using a quantitative descriptive approach, data were collected through surveys distributed to 45 service users. The analysis involved validity and reliability testing, classical assumption tests, simple linear regression, and hypothesis testing using SPSS version 24. The results indicate that responsiveness and empathy positively influence public satisfaction, accounting for 59.8% of the variance, while 40.2% is influenced by other factors outside the scope of this study. Among the two dimensions, empathy has a more dominant effect, with a regression coefficient of 0.596 and a significance level of 0.001 (p < 0.05), compared to responsiveness, which shows a coefficient of 0.270 and a significance level of 0.099. These findings suggest that personal attention, friendliness, and effective communication from service officers have a greater impact on satisfaction than service speed alone. The study implies that improving public service quality should prioritize strengthening empathy, interpersonal communication skills, and a human-centered service culture. This research also contributes theoretically by emphasizing service quality evaluation based on users’ direct experiences, providing a strategic foundation for developing more responsive and citizen-oriented public services.